Resuscitation effect of novel lyophilized platelets combined with lactated Ringer’s solution in rabbits with hemorrhagic shock and seawater immersion - DAI Chenglin; DU Wenqiong; TANG Ting (陆军军医大学学报)
‍Objective‍　‍To evaluate the resuscitation efficacy of novel lyophilized platelets (LP, thrombin-stimulated platelets) combined with lactated Ringer’s (LR) solution in rabbits with hemorrhagic shock and seawater immersion. Methods‍　‍Fifty rabbits were randomly assigned to 5 groups (Groups A, B, C, D and E, n=10). After all rabbits were anesthetized with 3% pentobarbital sodium at a dose of 1 mL/kg, soft tissue injury was inflicted in the left lower limb. The blood loss from the soft tissue injury was quantified after gauze hemostasis. The right lower limb was subjected to femoral artery catheterization, followed by blood withdrawal equivalent to 26% of the total blood volume of the rabbit. The rabbits were then vertically immersed in 3% artificial seawater, with the water level reaching above the xiphoid process, and were retrieved in 15 min later. Resuscitation strategies were applied to the rabbits from different group: Group A (no resuscitation), Group B (resuscitation with LR solution), Group C (resuscitation with LR solution and fresh platelets), Group D (resuscitation with LR solution and LP), and Group E (resuscitation with LR solution and novel LP). Coagulation function test, routine blood test, blood gas analysis, and thromboelastography were conducted at baseline and at 1, 2 and 4 h after injury. Results‍　‍The LP and rabbit model of hemorrhagic shock and seawater immersion were successfully prepared. At 1 h after injury, the mean arterial pressure (MAP) of Groups C, D and E (infused with platelet preparations) was significantly higher than that of Group A (without resuscitation, P<0.05); the lactate (Lac) content of Group C was obviously lower than that of Groups A and B (P<0.05); the base excess (BE) and blood urea nitrogen (BUN) levels of Groups C, D and E were notably lower than those of Groups A and B (P<0.05); and the prothrombin time (PT) of Group A was significantly longer than that of before injury (P<0.05). At 2 h after injury, the MAP of Groups C and D was significantly higher than that of Groups A and B, and that of Group E was notably higher than that of Group A (P<0.05); the Lac content of Groups C and E was obviously lower than that of Groups A and B, while that of Group D was also lower than that of Group A (P<0.05); the BE and BUN levels of Groups C, D and E were remarkably lower than those of Groups A and B (P<0.05); the maximum amplitude (MA) value of Group C was higher than that of Group A, while the value of Groups A and D at this time was significantly lower than the corresponding value before injury (P<0.05); and the activated partial clotting time (APTT) of Groups A and D was statistically longer than the corresponding baseline time (P<0.05). At 4 h after injury, the MAP of Groups C, D, and E was higher than that of Groups A and B, and that of Group B was higher than that of Group A (P<0.05); the Lac and BUN levels of Groups C, D, and E were lower than those of Groups A and B (P<0.05); the BE level of Groups C and D were lower than those of Groups A and B (P<0.05); the MA value of Groups B, C, and E were higher than those of Group A (P<0.05), while the MA value and APTT value of Groups A and D were significantly lower than their corresponding baseline values (P<0.05). Conclusion‍　‍For rabbits with hemorrhagic shock and seawater immersion, the novel LP combined with LR solution can significantly increase the MAP level, reduce Lac content, and sustainably maintain blood clot firmness and coagulation function.